A conflict of interests in electricity taxation? A micro econometric analysis of household behaviour - Bente Halvorsen; Runa Nesbakken (Statistics Norway, Research Department, 2002)
In conducting economic policy, governments generally face conflicts in various objectives, e.g. between efficiency and equity. In Norway, one objective of energy politics has been to reduce electricity consumption, and several tax increases have been proposed. Whether this objective may be in conflict with objectives of efficiency and equity is the focus in this paper. We discuss the effects on household behaviour of three different electricity tax schemes, one proportional and two non-linear. For each household we estimate the reduction in household electricity consumption. As measures of distributional effects and efficiency effects we estimate compensating variation and excess tax burden from the tax schemes. We find that the non-linear tax scheme targeting high electricity consumption is most preferred in order to reduce consumption and least preferred concerning the objective of minimizing excess tax burden. When considering distributional effects, the ranking of tax schemes depends on the weight placed on different household groups.
Keywords: D12; H22; D39; C31; 330; Household energy consumption; electricity taxation; distributional effects; excess tax burden; compensated variation; tax burden; linear expenditure system.